The treatment of oil palm empty fruit bunch fibre for subsequent use as substrate for cellulase production by Chaetomium globosum Kunze - Md. Shah, Umi Kalsom; Ariff, Arbakariya; H. S., Zulkifli; Tong, C. C.; Hassan, Mohd Ali; Abdul Karim, Mohamed Ismail (Elsevier Science, 1997)
The feasibility of using treated oil palm empty fruit bunch (OPEFB) fibre as a substrate for cellulase production by Chaetomium globosum Kunze was studied using a shaking flask fermentation system. The use of 2-mm chemically untreated OPEFB fibre increased cellulase production by about two times compared to 10-mm fibre. The effect of the different chemicals (NaOH, HCl, HNO3, EDA and EDTA) on the 2-mm fibre was also investigated. Treatment with these chemicals significantly (P < 0·05) increased the cellulose and reduced the lignin contents. Fermentation using OPEFB fibre treated with HNO3(0·5% v/v) gave the highest cellulase production and this was related to its high cellulose content. Cellulase production increased further when autoclaved (121°C, 15 psi for 5 min), chemically treated OPEFB fibre was used. When autoclaved 2-mm OPEFB fibre treated with HNO3 was used as a substrate, the maximum FPase activity and yield obtained were 0·95 U ml−1 and 120·7 U g−1 cellulose, respectively. The cellulase produced by C. globosum contained a high proportion of β-glucosidase. The ratio of specific activity of β-glucosidase to FPase was about 8. The production of all three major components of cellulase (endoglucanase, cellobiohydrolase and β-glucosidase) using pretreated OPEFB fibre were about three times higher than those obtained in fermentations using pure cellulose (Avicel and carboxymethylcellulose).